Dinghai fusheng records. 2 - Feitianyexiang (Fei Tian Ye Xiang. Dinghai Fusheng Records, 2025)
As winter descends, Chen Xing and Xiang Shu journey north beyond the Great Wall in search of the elusive Dinghai Pearl-only to find that the politics among the tribes of the Chi Le Covenant are just as treacherous as those of the Imperial Capital. But political strife is not the only danger that awaits them. Restless spirits stir awake, turning their journey into a battle for survival on the icy plains. As Chen Xing refuses to turn back and Xiang Shu struggles to balance duty and destiny, the path ahead grows ever more perilous-one that may force them to fight not just for their mission, but for each other.